Effect of the Number-Head Together Strategy on Academic Learning Outcomes of Secondary School Biology Students in Bichi Education Zone, Kano State, Nigeria - Musa, Mamuda Yusif; Abbas, Murtala; Muktar, Nasiru (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2024)
Available records from the Chief Examiners' Report of the West African Examination Council (WAEC, 2016 – 2019) and findings of many studies have revealed that Biology students in secondary schools of Bichi Education Zone performed inadequately in the Nervous system concept. Several of such studies attributed these inadequacies to improper teaching methods employed by teachers. Consequently, therefore, this study investigated the effects of the Number-Head Together (NHT) strategy on academic achievement and attitude in Biology among secondary school students in Bichi Education Zone, Kano-Nigeria. A pre-test, post-test nonequivalent, quasi-experimental design was used in the study. The study's population was made up of 4349 SS II Biology students (3352 males and 997 females) while the sample of the study consisted of 169 subjects from four intact classes drawn through a simple random sampling technique. The nervous System Achievement Test (NSAT) with a reliability index of 0.708 and the Student's Attitude toward Biology Questionnaire (SABQ) with a reliability index of 0.632 was used to measure students' academic achievement and attitude towards Biology respectively. The result of the study revealed that there was a significant difference in the mean academic achievement and attitude of Biology students in the two groups in favour of the experimental group. It was also discovered that there was no significant gender difference in the mean achievement and attitude scores of Biology students in the two groups. It was recommended that the NHT teaching strategy should be incorporated into secondary school curricula to enhance students' academic achievement and attitudes toward biology.